(untitled) (Scientific journal of the Fergana State University, 2024)
This article is devoted to the motives of German names, and its goal is a scientific analysis of the motives of German names and the factors influencing the choice of names. The article discusses ways to choose a name, including choosing a name based on family traditions, choosing a name based on the external influences of the language. Also, when choosing a name, the social status of the name giver was analyzed.